Study of the chemical and functional properties of Lipidium Sativum seeds - Neama Omar Bin Miskeen; Mohammad Abdullah Alshareef (Journal of Pure & Applied Sciences, 2022)
The cress seed is rich in protein and other Bioactive nutrients. In this study, the chemical and functional properties of cress seed powder was examined. The results showed that cress seed powder contains 6% moisture, 4% total ash, 22.66% protein, 18.36% crude lipids, 2 % water soluble ash, 2% insoluble ash in water. The percentage of vitamin C for garden cress seeds was 0.41 mg/g, and the percentage of acidity and pH of garden cress seeds were 0.768% and 8.93, respectively. Some functional properties of garden cress seed powder were also studied, and the results were 4.7mg/g water binding capacity, and 1.9mg/g oil binding capacity.